Prosperity gospels and enchanted worldviews: Two responses to socio-economic transformation in Tanzanian Pentecostal Christianity - Hasu, Päivi (Pentecostalism and development: Churches, NGOs and social change in Africa, 2012)
Following the remarkable global growth of Pentecostal churches, a body of research has developed that has been preoccupied with tracing the relationships between Pentecostalism, modernity and neoliberalism (Maxwell 1998, 2005, Meyer 1999, Gifford 2004, Robbins 2004). At the same time a parallel literature has developed that associates discourses about witchcraft in Africa with changing patterns of production and consumption and with new forms of wealth (Comaroff & Comaroff 1993, Geschiere 1997). In this literature, witchcraft has been accounted for in terms of moral economy; as a levelling force opposing new material inequalities, or conversely as a force in the accumulation of wealth and power (Geschiere 1997: 5). On the other hand, Pentecostalism has been shown to address issues of wealth and inequality, particularly through the so-called prosperity gospel, but also through its ideas of demonic agency (Maxwell 1998, Newell 2007: 463). An over-lapping theme in studies of both witchcraft and Pentecostalism has been their associations with individualist ideologies of modernity and with transformations of social relations and kinship. Both the spread of Pentecostalism and the resurgence of occult beliefs and practices have been related to economic transformations and the neoliberal economy.